The Role of Gut Microbiota—Gut—Brain Axis in Perioperative Neurocognitive Dysfunction - Lu, Jian; Hou, Wenlong; Gao, Sunan; Zhang, Ye; Zong, Youming (Frontiers in Pharmacology, 2022)
With the aging of the world population and advances in medical and health technology, more and more elderly patients are undergoing anesthesia and surgery, and perioperative neurocognitive dysfunction (PND) is receiving increasing attention. The latest definition of PND, published simultaneously in November 2018 in 6 leading journals in the field of anesthesiology, clarifies that PND is defined as perioperative cognitive impairment that occurs preoperatively and within 12 months postoperatively and meets the diagnostic criteria for neurocognitive impairment in the Diagnostic and Statistical Manual of Mental Disorders -fifth edition (DSM-5). PND is attracting more and more attention, though the specific pathogenesis of PND has not yet been fully elucidated. Recent studies have shown that gut microbiota regulates central nervous function and behavior through the gut microbiota - gut - brain axis, but the role of the axis in the pathogenesis of PND remains unclear. Therefore, this article reviews the mechanism of the role of gut microbiota-gut-brain axis in PND, so as to help explore reasonable early treatment strategies.